2009
DOI: 10.1590/s0066-782x2009000800016
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da estimulação ventricular convencional em pacientes com função ventricular normal

Abstract: SummaryBackground: The stimulation of the right ventricle (RV) may be deleterious in patients with ventricular dysfunction; however there is little evidence about the impact of this stimulation in patients with normal ventricular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
1
9
0
1
Order By: Relevance
“…With regard to clinical findings, the results as observed by Sa et al 48 were similar of the present study. Despite the non-use of questionnaires on quality of life, this study showed that patients remained assyntomatic, kepping the functional class I (NYHA).…”
Section: Conflict Of Interest Financial Support Referencessupporting
confidence: 92%
See 4 more Smart Citations
“…With regard to clinical findings, the results as observed by Sa et al 48 were similar of the present study. Despite the non-use of questionnaires on quality of life, this study showed that patients remained assyntomatic, kepping the functional class I (NYHA).…”
Section: Conflict Of Interest Financial Support Referencessupporting
confidence: 92%
“…Hearts presenting no significant structural alterations and with preserved systolic function may be able to offset the negative impact of mechanical dyssynchrony 48,49 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations